Optimization of Flavonoids Extraction from Vietnamese Male Papaya (Carica papaya, L.) Flowers by Ultrasound‐Asissted Method and Testing Bioactivities of the Extract. Issue 42 (16th November 2020) - Le Thao My, Phan; Van Luc, Tran; Do Dat, Tran; Hoai Thanh, Vuong; Khanh Duy, Huynh; Thanh Phong, Mai; Minh Nam, Hoang; Huu Hieu, Nguyen
Abstract: Papaya ( Carica papaya Linn.) is popularly cultivated in most tropical countries such as Malaysia, Vietnam, the West Indies, and throughout Africa. In the present work, an ultrasound‐assisted extraction (UAE) method has been developed for flavonoid extraction from Vietnamese male Carica papaya (C. papaya) flowers. Various influential operating parameters such as extraction time, ultrasonic power, solvent–to–material ratio, and extraction temperature on the flavonoid content were examined to optimize the extraction process. The result showed that under optimum extraction conditions including extraction time of 33 min, ultrasonic power of 240 W, solvent–to–material ratio of 27 : 1 mL/g, and extraction temperature of 46 ∘ C, the flavonoid content obtained was of 10.648±0.228 mg QE/g, which was found to be higher than that obtained by hot water extraction, enzyme‐assisted extraction, and ultrasound‐assisted enzymatic extraction methods. Therefore, UAE could be considered as the most efficient extraction method for flavonoids from Vietnamese male C. papaya flowers. In addition, the extract obtained under optimum conditions was tested bioactivities to prove the medicinal uses of flavonoids extracted from Vietnamese male C. papaya flowers with the half‐maximal inhibitory concentration values for antioxidant effect and anticancer effect against Hep‐G2 cell lines at 179.69 ± 0.03 and 56.63 ± 1.25 μg/mL, respectively. Abstract : This research illustrates the procedure of applying ultrasound‐assisted extraction method (UAE) for flavonoid extraction from Vietnamese male Carica papaya (C. papaya) flowers. Various influential operating parameters such as extraction time, ultrasonic power, solvent‐to‐material ratio, and extraction temperature on the flavonoid content were examined to optimize the extraction process. Besides, the extract obtained under optimum conditions was tested bioactivities to prove the medicinal uses of flavonoids extracted from Vietnamese male C. papaya flowers.